Issue Information. Issue 12 (28th December 2021) - Unknown
Abstract : Cover : RNA isolation is routinely carried out in many laboratories around the world for numerous downstream applications. In this issue, Oñate‐Sánchez and Verdonk describe a robust method for RNA isolation from multiple species. The approach, termed the Citrate‐Citric Acid RNA‐isolation (CiAR) method, is fast and efficient, and requires only two home‐made simple, inexpensive, and non‐toxic buffers. These buffers, which contain citric acid and its sodium salt, give the method its name. Image credit: Iris Fañanás‐Pueyo